Faktor Orang Tua dalam Memilih Taman Kanak-Kanak Bagi Anak Usia Dini - Melia Dwi Widayanti (SALIHA: Jurnal Pendidikan & Agama Islam, 2020)
For parents, choosing a school for their kids is something that cannot be simple. As a first institution that give a proper education, kindergarten should facilitate children’s ‘golden age’ to prepare them facing a real world . The aim of this study is to get information about what factor that parents should consider before they choose a suitable kindergarten for their beloved one. This research was using library research, which was a research method that using materials from library such as book and journal as a information source. Based on research, we can conclude that there are some factors that parents should consider, which was the location, cost, religious education partion, vision and mission, physical facilities, and teachers profile.